Building trust in the fresh produce industry - Batt, Peter (Massey University, 2001)
In the fresh produce industry, a grower's trust in their preferred market agent is derived primarily from the market agent's reputation. As a favourable reputation is derived from many satisfactory transactions where the grower believes that they have been adequately rewarded and treated fairly and equitably, there is a high correlation between satisfaction and trust. Market agent's have the opportunity to build trust by responding quickly to grower's complaints, by not engaging in opportunistic trading practices, and, through the provision of education and training programs, to ensure grower's fully understand the needs of customers.